INVESTIGATING HOW GENETIC, ENVIRONMENTAL, AND SOCIODEMOGRAPHIC FACTORS INTERACT TO PREDICT PRE-ECLAMPSIA: A CASE-CONTROL STUDY IN THE LOCAL GOVERNMENT AREA OF FUNTUA, KATSINA STATE, NIGERIA - HASSAN MUSA; POLITE DIKKE; RAYYAN MUHAMMAD GARBA; ABDULRAHMAN ABDULLAHI MOHAMMED; MOHAMMED ABDULLAHI MOHAMMED; USMAN MOHAMMED (International Journal of Health Research and Physical Study, 2026)
Pre-eclampsia, a serious pregnancy complication, presents notable hazards to the health of expectant mothers and newborns, especially in resource-constrained areas like the Funtua municipality Area in Katsina State, Nigeria. This study focuses on predicting pre-eclampsia in pregnant women in this region by investigating the interplay of environmental, genetic, and sociodemographic variables. Employing a case-control methodology, the research meticulously examines 100 patients diagnosed with pre-eclampsia and 100 control subjects. Through an in-depth review of medical records and highly structured interviews, the study collects comprehensive data on various risk factors, encompassing environmental exposures, genetic predispositions, and sociodemographic characteristics. The findings underscore the significant associations between these factors and the presence of pre-eclampsia, highlighting the complex interplay that contributes to its development. Notably, the study reveals increased odds of developing pre-eclampsia in younger (30 years) maternal age groups, with the highest odds ratio observed in women over 30 years. Furthermore, the research unveils differences in pollution exposure and dietary habits across maternal age groups, with a higher proportion of women under 20 years experiencing high pollution exposure and those in the 20-25 and over 30 age groups exhibiting unhealthy eating habits more frequently.